ANALISIS MANAJEMEN LOGISTIK ALAT KESEHATAN DI PMI KOTA BEKASI TAHUN 2022 - Hanifah Maulani (2022)
Good logistics management, besides being able to affect income and the blood service system in an agency, is one of the health care facilities. In addition to health service facilities, there are agencies that have gone unnoticed, namely agencies that support services and the smooth running of health care facilities, for example PMI Bekasi City which is in charge of providing blood stock for hospitals. But unfortunately the logistics management at PMI Bekasi City is still not running according to the standards of the PMI Central Blood Transfusion Unit. The method in this research is descriptive qualitative. The purpose of this study is to analyze and provide an overview of the logistics management system of medical devices that are not appropriate as material for advocacy and evaluation to decision makers at PMI Bekasi City in 2022. The results of this study are based on research that has been carried out related to logistics management of medical devices in PMI Bekasi City in 2022 it can be concluded that the input, process, and output aspects have been running according to the existing theory. However, the element that is most underlined is the part of the process, precisely the storage. Lack of movement space below 30%, lack of lighting, and other things that cause a decrease in the mobilization of logistics staff. So it is recommended to decision makers at PMI Bekasi City to prepare a storage room that is in accordance with the standards set by the Central PMI.